THE IMPACT OF THE ARAB SPRING ON THE PALESTINIAN QUESTION - Taffal, Asad (Przegląd Strategiczny, 2015)
The Palestinian question has been deeply influenced by regional political trends for the last six decades. Palestinians have been exposed to external and internal Arab politics, suffering – from the Lebanese civil war of 1976–1989, the Iranian Revolution of 1979, the Iraqi invasion of Kuwait in 1991, the American occupation of Iraq in 2003, and the Arab Spring since 2010. Those examples remind of the fragility of the Palestinian issue and its deep dependence on stability in the Arab World. The issue of present developments in the Arab region, the Israeli-Palestinian conflict, and the peace process in the Middle East are highly correlated.